P-457 Spindle transfer rescues poor embryo development of in vitro matured ovarian tissue oocytes from transgender men. (30th June 2022) - Christodoulaki, A; He, H; Zhou, M; Cardona Barberán, A; De Roo, C; Chuva De Sousa Lopes, S.M; Menten, B; Van Soom, A; De Sutter, P; Boel, A; Stoop, D; Heindryckx, B
Abstract: Study question: Could collection temperature and spindle transfer (ST) potentially improve development of embryos derived from in vitro matured (IVM) ovarian tissue oocytes (OTO) of transgender men? Summary answer: Spindle transfer, but not collection temperature, significantly improved embryo development of OTO-IVM oocytes from transgender men. What is known already: For transgender men, the fertility preservation strategy of ovarian stimulation may interfere with the desired masculine characteristics and enhance gender dysphoria. Alternatively, ovarian tissue oocytes collected ex vivo could serve as potential gametes, not requiring ovarian stimulation. Oocytes can be collected during gender affirming surgery, matured, and vitrified. Ovarian tissue oocyte in vitro maturation (OTO-IVM) has successfully been used for cancer patients, as live births have been reported. OTO-IVM in transgender men demonstrated sufficient maturation rates and survival following vitrification. Nevertheless, a decreased fertilization potential of these oocytes and severely compromised embryonic development have been observed. Study design, size, duration: Patients between 18-24 years were recruited for this study from November 2020 to September 2021. Ovaries from 14 transgender men were collected in either cold (4 o C, OTO-Cold) or warm (37 o C, OTO-Warm) collection medium, to verify the best collection method. Following ovarian manipulation, cumulus oocyte complexes (COCs) were harvested from spent medium and underwent maturation for 48hrs. ST was performed to overcome inferior fertilization and embryonic development. Participants/materials, setting, methods: Injected IVM oocytes underwent calcium imaging or were monitored for embryonic developmental potential. In vitro matured GV (germinal vesicle), MI (metaphase I) and in vivo matured oocytes with clusters of smooth endoplasmic reticulum (SERa) served as controls and cytoplasmic recipients for ST. OTO-IVM or control oocytes were used as spindle donors (ST-OTO or Control-ST respectively). Genetic analysis was performed to detect chromosomal abnormalities in embryos from all groups. Main results and the role of chance: In total, we collected 252 OTO-Cold and 230 OTO-Warm oocytes, showing similar maturation rates (53%). For calcium imaging, 39 control, 33 OTO-cold and 31 OTO-warm oocytes were analysed, determining the product of amplitude per frequency, in arbitrary units (AU). The average value for control oocytes was 2.30AU, significantly higher than OTO-Cold (1.47AU, p=0.046) and OTO-Warm oocytes (1.03AU, p=0.036). Calcium release was similar between OTO-Cold and OTO-Warm oocytes. Following ICSI, 19/47 OTO-Cold and 24/48 OTO-Warm oocytes normally fertilized, significantly lower than the control group (42/52) (p < 0.001 and p = 0.001 respectively). Blastocyst formation was significantly higher in control oocytes (13/42, 31%) when compared to OTO-Cold (1/19, p=0.027) and OTO-Warm (2/24, p=0.035). No statistically significant difference in fertilization rate and embryo development was detected between OTO-Cold and OTO-Warm oocytes. ST was performed to overcome poor embryo development in the OTO-Cold group. Following ST, 12/19 ST-OTO-Cold and 24/38 Control-ST oocytes were normally fertilized. Blastocyst development was similar between the two groups (4/12 and 7/24 respectively), but significantly higher than blastocyst development in OTO-Cold ICSI oocytes (p = 0.038 and p = 0.045). Genetic analysis revealed that 4/10 OTO-Cold, 4/11 OTO-Warm, 4/11 ICSI control, and 4/7 Control-ST embryos were chromosomally abnormal while 6/8 OTO-ST were abnormal, and 2/8 showed a suggestive low-grade mosaicism. Limitations, reasons for caution: A major limitation of our study is the lack of ovaries from cis women. Control oocytes used in this study originate from infertility patients that underwent ovarian stimulation. High abnormality rate in ST-OTO embryos might be concerning for the safety of ST, but the number of embryos analysed is limited. Wider implications of the findings: Our data indicate that OTO-IVM oocytes from transgender men display poor cytoplasmic quality, demonstrated by embryonic arrest and calcium imaging. ST was able to overcome poor embryo development, and it could be of interest to use freshly donated oocytes as cytoplasmic recipients for this. Trial registration number: Not applicable